Effects of physical exercise in adults with cardiovascular risk: Systematic review - Rojas-Aboite, Cristian Yovany; Hernández-Cortés, Perla Lizeth; Enríquez-Reyna, María Cristina; Gutiérrez-Arce, Kirby (Horizonte Sanitario, 2022)
Objective: To examine the effects of physical exercise on people’s health with cardiovascular risk and to explore their characteristics. Materials and methods: A systematic review study was developed. Clinical trials, experimental, quasiexperimetal and exploratory studies published from 2015 to 2021 were included. The PRISMA methodology was used. This review was conducted from May to July 2021, three databases were consulted: PudMed, Google Academic and Redalyc; The descriptors used were: Physical Activity, Cardiovascular Risk, Adults, using the Boolean operator "AND" to make connections between the descriptors. Results: Physical exercise showed a significant effect on cardiovascular risk factors, among these effects there was a decrease in blood pressure, glucose, cholesterol, triglycerides and body mass index. It was found that physical exercise performed constantly, with moderate or vigorous intensity reduces cardiovascular risk factors in adults, even when these people already have cardiovascular risk present. The most frequent interventions were: functional exercise, walking, running and cycling. Conclusions: The benefits of physical activity are not something to be explored again, however, it is relevant to identify the type of physical activity with greater acceptance and significant effects on the state of health. Keywords: Risk factors; Exercise; Intensity; Benefits